Molecular Dynamics Simulation Of Nano Wetting Of Lennard-Jones Droplet On Curved Surfaces - Alhiassah, Saleh Irsheid Saleh (2023)
This thesis aims to investigate the wetting behavior of LJ nanodroplets on curved surfaces using molecular dynamics (MD) simulations implemented in the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) package. The proposed methodology does not suffer the technical issues that plague experimental approaches. The thesis focuses on the influence of curved surface geometry and varying LJ interaction potentials on wetting transitions.